2019
DOI: 10.17236/sat00225
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between antral follicle count, blood serum concentration of anti-Müllerian hormone and fertility in mares

Abstract: The anti-Müllerian hormone (AMH) plays an inhibitory role during folliculogenesis by regulating the number of follicles entering the growing pool. Antral follicle counts (AFC) are highly correlated with serum AMH concentrations and both appear to be related to the ovarian reserve in several species. Few data on AMH and AFC in mares exist, especially with regard to fertility. Therefore, the objective of the current study was to investigate the interrelationship between antral follicle count, serum AMH concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…A large variation in circulating AMH levels was observed between mares, ranging from 0.6 to 4.1 µg/L. This result is in agreement with previous studies where serum AMH concentrations ranged from 0.22 ng/mL to 2.94 ng/mL in normal cycling mares [35], from 0.07 to 3.56 ng/mL in pre-ovulatory mares [46], and from 0.26 ng/mL to 15.47 ng/mL in mares irrespective of the reproductive state [42]. Circulating AMH levels have been suggested to be related to the population of follicles measuring 6 to 20 mm [26].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…A large variation in circulating AMH levels was observed between mares, ranging from 0.6 to 4.1 µg/L. This result is in agreement with previous studies where serum AMH concentrations ranged from 0.22 ng/mL to 2.94 ng/mL in normal cycling mares [35], from 0.07 to 3.56 ng/mL in pre-ovulatory mares [46], and from 0.26 ng/mL to 15.47 ng/mL in mares irrespective of the reproductive state [42]. Circulating AMH levels have been suggested to be related to the population of follicles measuring 6 to 20 mm [26].…”
Section: Discussionsupporting
confidence: 92%
“…However, it is worth mentioning that Traversari et al [46] did not find such a relation and that Uliani et al [42] observed a decrease in AMH concentrations only in mares older than 20 years. In agreement with previous observations, the correlation between the ovarian reserve and the amount of AMH in blood was shown to be stronger in older mares [26,46]. AMH levels were also positively correlated with the number of oocytes recovered in young and middle-aged mares.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…It has been reported that the antral follicle count (AFC), which is the amount of ovarian antral follicles, strongly correlates with the serum AMH levels and the number of primordial follicles. The AFC serves as an important marker of ovarian reserve ( Sakaguchi et al, 2019 ; Traversari et al, 2019 ). Therefore, we carried out morphometric analysis specific for distinct types of follicular populations.…”
Section: Discussionmentioning
confidence: 99%